A Prospective Study of Extracorporeal Shock Wave Lithotripsy (ESWL) Induced Hypertension in Lahore Division, Pakistan (Medical Forum Monthly, 2024)
Objective: Our aim was to evaluate the hypothesis in a randomized clinical trial, whether extra- corporeal lithotripsy (ESWL) causes any blood pressure change, in subjects with different genders having normal blood pressure and kidney lithiasis.Study Design: A descriptive cross sectional study.Place and Duration of Study: This study was carried out at the Department of lithotripsy, Khan Kidney Hospital and King Edward Medical University, Lahore from February 2012 to January 2013.Material and Methods: Adult patients (≤ 60 years old) were randomized to receive immediate ESWL versus observation. The trial included 100 patients with small (<20 mm) asymptomatic renal pelvic stones who were randomized to undergo ESWL. There were 25 male subjects (ESWL group A), 25 male subject (Control male group B), 25 female subjects (ESWL group C) and 25 female patients (Control female group D). Patients were evaluated by measure of the systolic and diastolic pressure before and after lithotripsy (immediately after the procedure & after 3 months of ESWL treatment). Hypertension was considered when diastolic pressure was greater than (≤90 mm/Hg). Blood pressure was recorded by using a standardized protocol. The amount of shock waves applied in each case ranged from 1500-6000, with the mean of 4000 shock waves at the median intensity of 15 kv. Patients were then followed up for measurement of blood pressure immediately after the treatment and after 3rd month. The rate of on set of hypertension was evaluated for all groups.Results: There was statistical significant difference in the incidence of hypertension between treated groups and observed groups.Conclusion: In this randomized controlled clinical trial, there was significant evidence that ESWL causes significant change in blood pressure (i.e. 12% in male group and 8% in female group).